Coronary Artery Spasm: The Interplay Between Endothelial Dysfunction and Vascular Smooth Muscle Cell Hyperreactivity - Hubert, Astrid (Eur Cardiol, 2020)
Patients with angina pectoris, the cardinal symptom of myocardial ischaemia, yet without significant flow-limiting epicardial artery stenosis represent a diagnostic and therapeutic challenge. Coronary artery spasm (CAS) is an established cause for anginal chest pain in patients with angiographically unobstructed coronary arteries. CAS may occur at the epicardial level and/or in the microvasculature. Although the underlying pathophysiological mechanisms of CAS are still largely unclear, endothelial dysfunction and vascular smooth muscle cell (VSMC) hyperreactivity seem to be involved as major players, although their contribution to induce CAS is still seen as controversial. This article will look at the role and possible mechanistic interplay between an impaired endothelial and VSMC function in the pathogenesis of CAS.